Distributions of dentists and physicians in Taiwan during the Japanese colonial period from 1923 to 1924 - Feng-Chou Cheng; Ling-Hsia Wang; Tzu-Chiang Lin; Julia Yu-Fong Chang; Chun-Pin Chiang (Elsevier, 2022)
Background/purpose: In 1896, the first dentist opened his dental clinic in Taipei City and this also opened a new era of Taiwan's dentistry. This study tried to assess the dentist manpower in Taiwan during the Japanese colonial period from 1923 to 1924, and hence to explore the appearance of Taiwan's early dentistry. Materials and methods: This study utilized the secondary data analysis to evaluate the numbers and distributions of dentists, physicians, and local practitioners in Taiwan from 1923 to 1924, to find the relationship among them, and further to explore the development of dentists in Taiwan at that period. Results: The total numbers of dentists and physicians increased from 87 to 882 in 1923 to 97 and 927 in 1924, respectively. Moreover, the total number of local practitioners decreased from 583 in 1923 to 558 in 1924. Their Gini coefficients for dentists, physicians, and local practitioners were 0.18, 0.16 and 0.20 in 1923 and 0.27, 0.05 and 0.19 in 1924, respectively. From 1923 to 1924, dentists and physicians were mainly concentrated in the northern and southern regions of Taiwan, and dentists had more serious uneven distribution problem. Conclusion: We conclude that the uneven distribution of dentist in Taiwan is an old problem. After a hundred years of development, the number of dentists increases at a higher rate than the number of physicians and there is no shortage of dentists to date in Taiwan. However, the problem of uneven distribution of dentists still exists and is even more serious now.